2015
DOI: 10.5296/ije.v7i4.8462
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure Causes of Students Error in Resolving Discrete Mathematics Problems Based on NEA as A Means of Enhancing Creativity

Abstract: <p>This article is based on research cooperation of Foreign Affairs in the first year, which was<br />carried out between the team of lecturers from the Department of Mathematics Education<br />Unnes (Indonesia) with Dr. Chin Kin Eng, a lecture of Mathematics Education from Universiti<br />Malaysia Sabah. The main objective of this research in the first year is to uncover the cause of<br />the students error in resolving Discrete Mathematics by Newman Errors Analysis (NEA). The<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
2
3
1
1
Order By: Relevance
“…The occurrence of these errors are generally less rigorous because students will be writing, students will be less rigorous calculation, and the haste students in doing. These results are similar to results of research conducted [3].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The occurrence of these errors are generally less rigorous because students will be writing, students will be less rigorous calculation, and the haste students in doing. These results are similar to results of research conducted [3].…”
Section: Discussionsupporting
confidence: 92%
“…In another study conducted in Indonesia by Junaedi [3], the result is a little different. Junaedi find the most common errors is at the stage of encoding and comprehension.…”
Section: Discussionmentioning
confidence: 87%
“…For this group of pupils, it seems that language poses a barrier to them in mathematics tasks presented in English. This however is in disagreement with the finding of Junaedi, Amin, Sugiharti and Chin (2015) whose study concluded that the pupils faced more problem in contentknowledge compared to language difficulties when tackling mathematical tasks in English.…”
Section: Discussioncontrasting
confidence: 75%
“…Kesalahan yang dilakukan oleh siswa diantaranya adalah siswa tidak bisa menentukan rumus, kesalahan dalam menghitung, kesalahan dalam mengubah informasi ke dalam bentuk matematika, miskonsepsi dan kelalaian dalam menuliskan kesimpulan (Farida, 2015). Kesalahan yang dilakukan siswa dalam menyelesaikan soal matematika diantaranya, siswa tidak tahu arti dari simbol atau istilah, masalah, tidak tahu formula atau rumus yang digunakan, siswa tidak bisa membuat algoritma pemecahan masalah secara berurutan dan benar, siswa tidak bisa menjawab sesuai pertanyaan (Junaedi, Suyitno, Sugiarto, & Eng, 2015).…”
Section: A Pendahuluanunclassified